Uji Toksisitas Subkronis Ekstrak Etanol Daun Pucuk Merah (Syzygium Myrtifolium Walp.) Terhadap Fungsi Hati Dan Ginjal - Syilfia Hasti; Rahmayati Rusnedy; Musdalifah Musdalifah; Asnila Asnila; Lisa Renita; Ferelina Santi; Shella Anggraini; Novia Sinata (Fakultas Farmasi Universitas Pancasila, 2022)
For the development of natural medicines from the ethanolic extract of Syzygium myrtifolium Walp leaves it is necessary to know the pre-clinical safety test so that its safety if used in the long term. The subchronic toxicity test of the ethanolic extract of Syzygium myrtifolium Walp leaves l was carried out by assessing the kidney and liver function of the test animals given after 60 days of test preparation, in the form of blood biochemical examination using the Mindray®BA-88A device and histological examination of the kidneys and liver. The results showed that the administration of ethanol extract of Syzygium myrtifolium Walp leaves at doses of 300, 600 and 900 mg/kgBW did not significantly affect the activity of SGOT, SGPT, serum creatinine levels (p>0.05). Microscopically on the percentage of damage to the glomerulus of the right and left kidneys. at doses of 600 and 900 mg/kgBW there was a significant difference to the control group (p<0.05). For qualitative microscopic examination, namely observation of sinusoids and hepatocyte cells at each level, there were abnormal changes. Meanwhile, quantitative microscopic examination at doses of 600 and 900 mg/kgBW caused an increase in the percentage of central vein damage (p<0.05). From the research, it was found that the ethanolic extract of Syzygium myrtifolium Walp leaves of white mice was safe for liver and kidney function at a dose of 300 mg/kgBW, but the doses group of 600 and 900 mg/kgBW gave a toxic effect on the kidneys and liver when compared to the control group.